PROSPECTS OF INTEGRATION OF AQUACULTURE WITH ANIMAL HUSBANDRY AND LAND CROP CULTURE IN TRIPURA STATE - BISWAS, B. K.; ACHARYA, P. (Journal of Indian Fisheries Association, 2015)
Tripura is a densely populated small state with meagre water resources. 47.51% of the population is constituted by socio-economically backward, illiterate, orthodox, tribals and Scheduled Castes. Some of them are nomad and a majority of the rest of the populaiton is refugees from Bangladesh, but almost 100% is fish eater. Settlement of tribals in villages, provision of nutritious food and employment therefore calls for proper utilization of every resource they have. The State is poor in water resources but recently has created 21,636.23 ha of new water area. Tripura is rich in pig population, besides poultry birds. Paddy is the main crop cultivated in arable lands. An integration of live stock raising and land based agriculture with pisciculture practices around mini barrages will help in solving the problems to a great extent. The paper is an attempt to outline the prospects of integration of aquaculture with animal husbandry and land based crop culture in Tripura State.